2016
DOI: 10.1016/j.jmb.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment, Duplex Unwinding and Protein-Mediated Inhibition of the Dead-Box RNA Helicase Dbp2 at Actively Transcribed Chromatin

Abstract: RNA helicases play fundamental roles in modulating RNA structures and facilitating RNA-protein (RNP) complex assembly in vivo. Previously, our laboratory demonstrated that the DEAD-box RNA helicase Dbp2 in S. cerevisiae is required to promote efficient assembly of the co-transcriptionally associated mRNA binding proteins Yra1, Nab2, and Mex67 onto poly(A) + RNA. We also found that Yra1 associates directly with Dbp2 and functions as an inhibitor of Dbp2-dependent duplex unwinding, suggestive of a cycle of unwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 81 publications
(129 reference statements)
2
27
0
Order By: Relevance
“…In contrast to AtNDX, Yra1 is an RNA-binding protein that presumably affects R-loop dynamics by binding to the RNA-DNA hybrids, likely impeding the action of helicases and RNase H and leading to the accumulation of stable or more persistent R loops. Indeed, Yra1 inhibits loading of Dbp2, an RNA helicase with in vitro RNA-DNA-unwinding activity (Ma et al 2013(Ma et al , 2016. However, the in vitro ssDNA-binding ability observed for Yra1 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to AtNDX, Yra1 is an RNA-binding protein that presumably affects R-loop dynamics by binding to the RNA-DNA hybrids, likely impeding the action of helicases and RNase H and leading to the accumulation of stable or more persistent R loops. Indeed, Yra1 inhibits loading of Dbp2, an RNA helicase with in vitro RNA-DNA-unwinding activity (Ma et al 2013(Ma et al , 2016. However, the in vitro ssDNA-binding ability observed for Yra1 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…54,55 Dbp2 is a co-transcriptional RNA chaperone and bona fide RNA helicase whose activity is necessary for assembly of RNAbinding proteins, Yra1, Mex67, and Nab2 onto poly(A) C RNAs. 56,57 During transcription, both messenger and long non-coding RNAs are co-transcriptionally bound with a set of RNA-binding proteins to form a ribonucleoprotein complex (RNP), which then undergoes a variety of processing steps, including capping, splicing, termination, and polyadenylation. Loss of DBP2 also results in over-accumulation and 3 0 extension of the GAL10s lncRNA, 58 suggesting a connection between Dbp2 and proper biogenesis of the GAL lncRNAs.…”
mentioning
confidence: 99%
“…1). RNA helicases participate in alteration in conformation of ribonucleotides, RNPs, mRNP assembly and pre-mRNA splicing (Hartman et al, 2006;Jankowsky, 2011;Owttrim, 2013;Mallam et al, 2014;Ma et al 2016). RNA helicases also plays essential role in cell signaling against viral infection by activating interferons and cytokines through phosphorylation of the transcription factors ).…”
Section: Rna Helicasesmentioning
confidence: 99%
“…Till date a lot of researches have been done in abiotic stress and its effect on various plants which have revealed that somatic embryogenesis is induced by stress (Grafi and Barak, 2015). It has also been proven that abiotic stress induces dedifferentiation which is characterized by remodelling of chromatin structure into a transcriptionally active open conformation that may increase the expression of some stress responsive genes (Koroleva et al, 2009b;Grafi and Barak, 2015;Ma et al, 2016). When plants are exposed to abiotic stress conditions, some specific cell signaling events occur to activate transcription factors which bind to the promoter region of stress responsive genes to show either positive or negative regulation in abiotic stress (Gong et al, 2002;Kant et al, 2007;Barak et al, 2014;Asensi-Fabado et al, 2016).…”
Section: Abiotic Stress and The Dead-box Rna Helicasesmentioning
confidence: 99%